การพัฒนาระบบประเมินผลการผลดำเนินงานของฝ่ายออกแบบในบริษัทที่ปรึกษา - กิตติ เดือนหงาย (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The design works during pre-construction phase is crucial because the design problem such as defective design could lead to several problems during construction phase. To mitigate the design problems, the previous research have proposed many methods, tools, and principals to improve the performance of design work. Nevertheless, one important procedure which ensures the quality of design work after applied those tools, policies, or principals in organisation is the performance measurement and evaluation. This research aims to develop the tools for measuring and estimating performance of design team. The research methodology began with developing the list of suitable quantitative indicators by literatures review and interviewed 19 designers in consulting companies with delphi technique. Next the research collected the performance evaluating criteria from 19 designers and determined the important weight of each indicator from seven designers. Then the research collected the rule base conditions from ten designers and developed the fuzzy evaluation system. Lastly the system was tested with 13 design projects. The research results found nine indicators which were categorized into five main groups. These are cost controlling ability of design team, time controlling ability of design team, quality of design documents, productivity of design team, and the enthusiastic and response of design team. In addition, the results of using the system with case studies found the percent error in the acceptable level.